2010
DOI: 10.1111/j.1751-553x.2008.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laboratory detection methods of aspirin resistance in coronary artery disease patients

Abstract: Aspirin reduces the prevalence of nonfatal myocardial infarction, stroke, and death by 25.0% in high risk group of patients with cardiovascular disease. Previous studies have estimated that about 5.5-56.8% of the population are aspirin resistant. The mechanisms of aspirin resistance (AR) have not been fully understood. We compared the detection methods for AR using traditional platelet aggregometry and VerifyNow system. One hundred and seventy-two coronary artery disease patients who had taken aspirin only or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Nonresponsiveness to antiplatelet drugs remains a major limitation in the prevention of future thrombotic episodes in patients who experience acute coronary syndrome (ACS). Previous studies estimated that 5.5% to 56.8% of the population are aspirin resistant (1), and the prevalence of clopidogrel nonresponsiveness was 21% (2). Although fewer published data are available for dual (aspirin and clopidogrel) nonresponsiveness, the incidence in a recent study involving 746 patients was only 6% (3).…”
Section: Discussionmentioning
confidence: 96%
“…Nonresponsiveness to antiplatelet drugs remains a major limitation in the prevention of future thrombotic episodes in patients who experience acute coronary syndrome (ACS). Previous studies estimated that 5.5% to 56.8% of the population are aspirin resistant (1), and the prevalence of clopidogrel nonresponsiveness was 21% (2). Although fewer published data are available for dual (aspirin and clopidogrel) nonresponsiveness, the incidence in a recent study involving 746 patients was only 6% (3).…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of aspirin resistance varies from study to study, ranging from about 5% to 60% [9,15,28]. A meta-analysis of 52 full-text studies covering 8364 ischemic stroke/TIA patients on aspirin or clopidogrel revealed that the prevalence of high ontreatment of platelet reactivity to aspirin is 23% [8].…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper also discussed findings along these same lines; the researchers concluded that the prevalence of aspirin resistance depends on the type of test and agonist used. 13 In this study, aspirin effects on platelets using WB tested on conventional aggregometry (Chrono-Log aggregometer) could be determined by the absence of aggregation with AA, reduced ATP release with AA, and reduced aggregation with ADP and ristocetin. Although qualitative changes (ie, saw-tooth appearance) on ristocetin tracing did not yield significant findings, an association with platelet response to aspirin was observed.…”
Section: Discussionmentioning
confidence: 99%